2002
DOI: 10.1034/j.1600-0773.2002.910614.x
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Functions in Gastrin Gene Knock‐Out Mice

Abstract: The gastric hormone gastrin was the 2nd hormone to be identified and was initially recognized for its ability to induce acid secretion. Following the purification and subsequent development of specific radioimmunoassays for gastrin, it was also shown to be a regulator of oxyntic mucosal growth. To explore the importance of gastrin or its receptors for gastric development and gastric physiology both have been knocked out. The knock-out mice are viable, develop with any gross abnormalities, and are fertile. Even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 41 publications
0
5
0
1
Order By: Relevance
“…SOM acts as a potent inhibitor of gastric acid secretion. In gastrin gene knockout mice, a reduction in the number of parietal cells was observed, whereas the EEC number was not affected by gene deletion [ 84 , 85 , 86 , 87 ]. In our study, we showed an increase in SOM-IR cells in fish fed a diet supplemented with EOs.…”
Section: Discussionmentioning
confidence: 99%
“…SOM acts as a potent inhibitor of gastric acid secretion. In gastrin gene knockout mice, a reduction in the number of parietal cells was observed, whereas the EEC number was not affected by gene deletion [ 84 , 85 , 86 , 87 ]. In our study, we showed an increase in SOM-IR cells in fish fed a diet supplemented with EOs.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the absence of Rb protein caused by heterozygous germline mutation induces childhoodonset retinoblastoma in a high percentage of humans. Surprisingly, the same phenomenon in mice induced the development of pituitary carcinomas (Jacks et al 1992, Vooijs et al 1998, 2002. Similarly, the role of p19, encoded by Cdkn2b, as a tumor suppressor in regulating pituitary anterior lobe proliferation has been revealed by a conventional knockout mouse model of Cdkn2b, as these knockout mice developed multiple tumor types including PRL-, GH-and FSH-secreting PAs (Bai et al 2014).…”
Section: Models Of Pituitary Tumorsmentioning
confidence: 96%
“…Because of this, it is considered a valuable model of stomach GEP-NET development in combination with other agents, like H. pylori or H. felis. Strikingly, the genetic ablation of gastrin in the gastrin-deficient mice (Friis-Hansen et al 1998) also results in the development of spontaneous gastric cancer at few weeks of age (Friis-Hansen 2002), suggesting that any dysregulations of gastrin production may lead to oncogenic growth.…”
Section: Models Of Neuroendocrine Tumorsmentioning
confidence: 99%
“…Gastrin, which is produced by G cells in the antral mucosa, is a crucial regulatory hormone in the gastric mucosa and can regulate cell division, invasion, angiogenesis, and anti-apoptotic activity at the transcriptional level 142,143. It functions to regulate acid secretion in response to feeding and in maintaining developmental epithelial cell homeostasis in the fundic and antral mucosa.…”
Section: Genetically Engineered Mouse Modelsmentioning
confidence: 99%